Congenital giant folliculosebaceous cystic hamartoma of thigh: A rare case - Vedita Madhukar Bobde; Satish B Helwatkar; Prajakta R Sathawane; W K Raut (Wolters Kluwer Medknow Publications, 2019)
Hamartomatous conditions of skin are comprised of variable composition of normal skin elements. They can present as nodular masses. They can be mistaken for neoplastic skin lesions. Folliculosebaceous cystic hamartoma is a rare skin condition seen in adults, commonly on head, neck and face region. Congenital variant is rare. Only few case reports have been described in literature occurring on sites other than face. Definitive diagnosis can be given only on histopathology. We report a case presenting as thigh mass in a 1 year old female child clinically diagnosed as papilloma of skin.